2019
DOI: 10.3928/01913913-20190128-02
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma Incidence Trends in Canada: A National Comprehensive Population-Based Study

Abstract: Purpose: To determine the incidence rates and geographic distribution of retinoblastoma in Canada to aid cancer control programs. Methods: Patients with retinoblastoma whose data were available from the Canadian Cancer Registry (CCR) and Le Registre Québécois du Cancer (LRQC) were studied. Using third edition International Classification of Diseases for Oncology (ICD-O) codes, the authors examined the incidence rates and geographic distribution of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…Studies have shown that choroidal invasion can predict presence of metastasis more reliably than optic nerve invasion. In the series of Darwich and associates [32], it was reported that patients with choroidal invasion were more likely to develop systemic metastasis compared to the ones with or without optic nerve invasion ( P =0.0001). Choroidal invasion has also been found to correlate with molecular prognostic markers such as TP53 unlike other high risk factors (HRF) as it was once reported by Seema and associates [33] in India.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that choroidal invasion can predict presence of metastasis more reliably than optic nerve invasion. In the series of Darwich and associates [32], it was reported that patients with choroidal invasion were more likely to develop systemic metastasis compared to the ones with or without optic nerve invasion ( P =0.0001). Choroidal invasion has also been found to correlate with molecular prognostic markers such as TP53 unlike other high risk factors (HRF) as it was once reported by Seema and associates [33] in India.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence and mortality data for oral cavity and oropharyngeal malignancies were extracted from 3 distinct but complementary population-based cancer databases (Canadian Cancer Registry [CCR], Le Registre Québécois du Cancer [LRQC], and Canadian Vital Statistics [CVS]) using the previously reported and established methods. 11 -34…”
Section: Methodsmentioning
confidence: 99%
“…Incidence data were collected from the Canadian Cancer Registry (CCR) and Le Registre Québécois du Cancer (LRQC) databases and mortality data from the Canadian Vital Statistics (CVS), as previously reported. [13][14][15][16][17][18][19][20][21][22][23][24][25][26]…”
Section: Methodsmentioning
confidence: 99%